Therapeutic options in inoperable ROS1-rearranged inflammatory myofibroblastic tumor of the tongue in a child: a case report and literature review. Issue 10 (17th July 2021) - Styczewska, Malgorzata; Patel, Agastya; Jaskulowska, Joanna; Godzinski, Jan; Swieton, Dominik; Wasag, Bartosz; Dass, Juliea; Bien, Ewa; Krawczyk, Malgorzata A.
Abstract : Inflammatory myofibroblastic tumor (IMT) is a rare borderline malignancy, usually treated with surgery only. Exceedingly rare cases of inoperable, recurrent, or metastatic IMTs pose a therapeutic challenge. We report successful treatment of a 7-year-old girl with an inoperable anaplastic lymphoma kinase (ALK)-negative IMT of the tongue. The patient underwent various anti-inflammatory (steroids, nonsteroidal anti-inflammatory drugs, clarithromycin) and antiproliferative (chemotherapy) therapies to enable tumor regression and complete resection. Ultimately, next-generation sequencing of the tumor revealed a TFG-ROS-1 translocation, allowing for an off-label targeted therapy with crizotinib. Crizotinib treatment caused slight tumor regression but evident change of its structure, allowing for complete non-mutilating resection. Two histopathology examinations revealed complete disappearance of neoplastic cells following therapy. The patient remains disease-free 22 months after the delayed surgery. In children with inoperable ALK-negative IMTs, molecular testing must be performed to identify other targetable oncogenic fusions, including TFG-ROS1.